Orientation of a Trametes versicolor laccase on amorphous carbon nitride coated graphite electrodes for improved electroreduction of dioxygen to water. (1st July 2018) - Blout, Achraf; Billon, Florence; Calers, Christophe; Méthivier, Christophe; Pailleret, Alain; Perrot, Hubert; Jolivalt, Claude
Abstract: Amorphous carbon nitride (a-CNx) thin films were used for the first time as electrode materials in the elaboration of biofuel cell cathodes as a consequence of i) the natural presence of amine type functional groups and ii) the ease to generate carboxylic acid groups on their surface with the help of an anodic treatment. Their rich surface chemistry was exploited to investigate the influence of the orientation of immobilised laccase on their bioelectrocatalytic activity towards oxygen reduction reaction (ORR) in a direct electron transfer configuration. Among four different immobilisation strategies leading to a statistical control of the orientation and tested in this work, spontaneous adsorption of natural laccase on pristine a-CNx provided the smallest current density value (3.5 μA cm −2 ) whereas covalent grafting of oxidised laccase on anodically treated a-CNx via imine and amide bond formation using a coupling agent led to a much higher but still low 44.6 μA cm −2 current density. This substantial improvement of the current density value measured for ORR confirms that the orientation of immobilised laccase exerts a measurable influence on its bioelectrocatalytic activity towards ORR. In parallel, the surface coverage rate of enzymes showing such activity was estimated as a function of the immobilisation method by using four different techniques (current density, activity towards ABTS, XPS and AFM). It was found that only a small fraction (7.1% to the most) of the electrode surface is covered with active enzymes, whatever the immobilisation method, whereas an enzyme population corresponding (almost) to a full enzyme monolayer was actually immobilised. This observation is crucial because it strongly suggests that the development of innovative immobilisation strategies allowing an increase of the active enzyme fraction through a simultaneous optimisation of the bioelectrocatalytic activity of the enzyme and of its electronic communication with the electrode offers much more promising perspectives than the control of the orientation of the immobilised enzyme population on its own.